Pharmacokinetics and pharmacodynamics of ritodrine hydrochloride administered orally and intramuscularly to female healthy volunteers - Marzo, Antonio; Coa, Katrin; Fontana, Elena; Tavazzi, Simona; Bo, Lorenzo Dal; Ismaili, Shefqet; Zava, Dario; Cantoni, Vittorio; Bertolini, Andrea (Arzneimittelforschung, 2010)
Ritodrine hydrochloride ((R,S)–4-hydroxy-β-[1-[2-((4-hydroxyphenyl)ethyl]amino)ethyl]benzenemethanol, CAS 26652-09-5) is a direct-acting sympathomimetic agent with a predominant β-adrenergic activity and a selective action on β2-receptors. A clinical trial was carried out to investigate the pharmacokinetics, pharmacodynamics and safety of ritodrine hydrochloride administered at the dose of 10, 20 and 30 mg p.o. and 10 mg by i.m. route. A four-way randomised crossover design was adopted on 12 health female volunteers with a wash-out of a least 14 days. Concentrations of ritodrine and of the pool of ritodrine in plasma and concentrations of the pool of ritodrine in urine of volunteers were bioassayed with tandem mass spectrometry. The following pharmacokinetic parameters wer calculated, using the non-compartmental model: Cmax, AUC0–t, AUC0–INF, t1/2, Vd/f, and Aet after each administration. The distribution volume of ritodrine proved to be about 3 times higher than that of the pool of ritodrine after i.m. injection confirming the good permeability of ritodrine that massively enters tissue compartments. Statistical analyses of phar-macokinetic parameters ascertained that the p.o. absorption of ritodrine hydro-chloride was linearly related with the doses administered in the 10–30 mg range. The pharmacodynamic parameters evaluated complied with the mechanism of action of this drug.
Keywords: CAS 23239-51-2; Ritodrine, i.m. absorption, pharmacodynamics, pharma-cokinetics, p.o. absorption; Sympathomimetic agent